ANALISIS TINGKAT KESEHATAN KOPERASI JASA KEUANGAN SYARIAH BAITUL MAAL WAT TAMWIL DENGAN METODE CAMEL - ANDRIANI SYOFYAN; ERVINA ERVINA (Maqdis: Jurnal Kajian Ekonomi Islam, 2017)
The theme of the article is "economy based on the principles of Islam". This study aims to determine the level of health KJKS BMT Padang City, especially KJKS BMT Kelurahan Batuang Taba, KJKS BMT Kelurahan Padang Besi, and KJKS BMT Village Kubu Parak Karakah by using CAMEL method. This study uses a quantitative approach supported by the use of descriptive statistical analysis. The method used is CAMEL (Capital, Asset, Management, Earning, and Liquidity). This method contains the steps assessed by calculating the magnitude of each ratio on the components. The goal is to simplify the information that describes the relationship between these components so that information can be obtained quickly and accurately. This is absolutely done because CAMEL method is only oriented to the financial statements only, so it is known how the level of health owned by each KJKS BMT. The results of this study indicate in general can be concluded that the assessment of health level KJKS BMT Padang with CAMEL method is in a fairly healthy condition. Where of the three KJKS BMT Padang city studied two are in a fairly healthy position even though one in healthy condition.